Enhancement of code division multiple access system performance using raptor codes - Ikhlas Mahmoud Farhan; Dhafer R. Zaghar; Hadeel Nasrat Abdullah (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
Some kinds of communication systems work in very low signal-to-noise (LSNR) environments. For these systems to function reliably, specific techniques and methodologies have to be used to mitigate the degrading effects of the channel. The channel coding method is the key element in most LSNR communication systems, but emphasizing the code division multiple access (CDMA) is a new transmission technique in these channels. To enhance the CDMA scheme's system capacity and reach unprecedented ranges of LSNR values in wireless sensor network. This paper suggests combining CDMA with certain types of channel coding algorithms, such as the raptor codes. The raptor channel encoding technique has improved the CDMA system's performance when using binary phase-shift keying (BPSK) modulation in additive white gaussian noise (AWGN) channels. It has achieved a low bit error rate in range of 10-7 at Eb/No value of (-3) dB and about 10-6 at shannon's limit. The Raptor-coded CDMA scheme works well for channel signal to noise ration (SNR) values of greater than -9 dB, showing an improvement of about 7 dB compared with turbo/convolutional channel coding methods used with the CDMA system bit error rate (BER) and throughput. On the other hand, it has been shown that the convolutional encoder presents the weakest performance compared to both the turbo and raptor codes.